Analysis of Culinary MSME Business Performance through Digital Entrepreneurship Academy (DEA) Training in South Kalimantan - Sudirwo Sudirwo; Syahrial Shaddiq (Budapest International Research and Critics University, 2023)
This research focuses on examining the impact of the benefits provided by the Ministry of Communication and Informatics (Kemenkominfo) with data collected from Micro, Small and Medium Enterprises (MSMEs) in the South Kalimantan (Kalsel) region during the coronavirus disease 2019 (COVID-19) pandemic, especially MSMEs in the culinary industry. The aim of this research is to ascertain how training, which is mediated by digital marketing skills and entrepreneurial motivation, influences business performance both directly and indirectly. Quantitative method used in this research. In order to collect data online, a survey from Google Form was given to respondents who were alumni of the 2021 DEA training participants in the South Kalimantan region as many as 47 people as a sample of a total population of 115 people. At least Roscoe's 30% of the total population was used to determine the sample size. SmartPartial Least Square (SmartPLS) 3.0 with path analysis test, a statistical tool used in data processing. The results of the descriptive analysis showed an increase in business turnover of 85.11%, both before and after the respondents participated in DEA activities. Based on the findings of the quantitative analysis, the exogenous variable DEA Training (X) has a positive and significant effect on the endogenous variable MSME Business Performance (Y), as well as the mediating variables Digital Marketing Capability (Z1) and Entrepreneurial Motivation (Z2). The indirect effect of all variables is beneficial but not statistically significant on MSME Business Performance, this indicates that there are additional factors other than the mediating variable that significantly affect business performance. For example, respondents may have additional skills and methods of running a business. Considering that there is no research on the DEA program for MSME actors, this research offers a new perspective to the Ministry of Communication and Informatics of the Republic of Indonesia